EFL Teachers’ Perceptions of Digitalization in Algerian Higher Education: a Case Study at Badji Mokhtar University (Revue El-Wahat pour les Recherches et les Etudes, 2026)
This article examines the perceptions of English as Foreign Language (EFL) teachers regarding the integration of digitalization within Algerian higher education, with a particular focus on Badji Mokhtar University in Annaba. The study is motivated by the increasing national and global emphasis on digital education, especially following the COVID-19 pandemic, and the challenges faced in aligning Algerian higher education with international standards. Using a qualitative approach based exclusively on structured interviews with five EFL teachers, the research investigates their digital competence, their use of digital platforms, and the perceived benefits and barriers of integrating technology in the classroom. The findings highlight that while teachers value digitalization for its flexibility, access to resources, and ability to foster learner autonomy, they remain hindered by infrastructure limitations, insufficient institutional support, and low levels of student engagement. The study emphasizes the urgency of strengthening training and institutional policy, and it recommends the adoption of blended learning models as a sustainable path forward for Algerian universities.